Human Nature in the View of the Qur'an and Ibn Arabi - Hendra Albimawi; Tobroni; Moh. Nurhakim (Universitas Muhammadiyah Palu, 2023)
This research consists of primary data and secondary data; First, primary sources, namely data collected by researchers or data takers directly from the source in the form of verses of the Koran relating to human nature. The secondary data is the result of academic research that discusses human nature. This research use desciptive qualitative approach. Theoretically, this approach is used to investigate circumstances, conditions, or other elements related to the research subject. findings in this study, humans have two dimensions: material and immaterial. The Qur'an shows that the human concept consists of five categories, namely: (1) al-insan, (2) al-ins, (3) al-nas, or unas, (4) al-basyar and (5) ) bany Adam. Despite the fact that these three words stand out the most in a human context, each has a different meaning. Allah, Who created everything in the best way possible, started the creation of man from a clot of blood and created his offspring from lowly water as a kind of essence, then perfected the process of his creation. Death destroys the elements of the body, but the elements of the soul will remain and rise again at the end of time. He is composed of a combination of two elements; spirit and body. If someone only knows the land part and ignores the part that is breathed by God's spirit, then they will not understand the basis of human beings. Ibn Arabi often expressed this idea by using the terms